Between auteurism and sponsored cinema: Joris Ivens, Bernardo Bertolucci and ENI. Issue 2 (1st March 2019) - Peretti, Luca
Industrial and sponsored cinema played a pivotal role in film history, a role that has yet to be fully recognized in the study of Italian cinema. In Italy, the former state-owned oil company, Ente Nazionale Idrocarburi (National Hydrocarbons Authority) (ENI), sponsored films of different kinds, including two films made in the 1960s by major directors: the Dutch director Joris Ivens and the young but already-established Bernardo Bertolucci. By focusing on Ivens' L'Italia non è un paese povero (Italy is not a Poor Country) (1960) and Bertolucci's La via del petrolio (The Path of Oil) (1967) this article discusses the relationship between sponsored cinema and auteurism, and in particular how author theory (or 'practice') became important in Italian film studies and in the pioneering work of Millicent Marcus.